Impact of propylene glycol supplementation during early postpartum period on serum me tabolites and reproductive performance in Nili-Ravi buffalo - Muhammad Saleem Akhtar; Rehman Khan; Ejaz Ahmad; Tanveer Ahmad; Aijaz Ali Channa; Muhammad Irfan ur Rehman Khan (Revista Científica)
The present study investigated the effect of propylene glycol supplementation during the early postpartum period on serum metabolites in buffalo. Nili Ravi buffalo (n=25) were randomly assigned to one of two groups, i.e., Treatment Group (n=15) and Control Group (n=10). In the experimental group, propylene glycol (500 ml/  animal/ day) supplementation started from day 7 to day 50 postpartum. These animals were under observation for weekly measurements from 3 weeks pre-partum to 10 weeks postpartum. Blood sampling was done weekly for glucose, insulin, and beta-hydroxybutyric acid analysis. Propylene glycol supplementation did not affect body weight and milk yield (p> 0.05). Serum glucose and insulin concentration were significantly increased (p< 0.05), and ketone body levels were reduced (p< 0.05) shortly after propylene glycol supplementation. It was concluded that propylene glycol during the early lactation period in Nili-Ravi buffalo effectively increased serum glucose and insulin levels and lowered blood ketone body levels, which reduced the risk of ketosis.